ARTISTIC PICTURE OF THE WORLD IN THE NOVEL “THE STONE MAPLES” BY LENA ELTANG - Михайлова, Галина; Самойленко, Александра (Literatūra, 2013)
The article deals with the category of the “artistic picture of the world” and analyzes the way and elements of the personal thinking and world perception of Lena Eltang, which are reflected in her novel “The Stone Maples”. It also emphasizes her individual concepts and characteristics which make Eltang an extravagant and contemporary writer.The main challenge of the novel is to confront the text, fiction, and reality. The novel is constructed as a mosaic of the texts with different subjects of speech. So, the novel represents the complicated structure of the picture of the world, which offers a variety in thinking and perceiving the reality. The article reviews both space and time continua (namely the past motive, memory, world oppositions, and others) and the use of “text-in-the-text” technique, introduction of the semantics of the “possible worlds”, ideas of virtual reality, etc. The interior space of the novel is composed of equal “small” spaces. The chaos of the time coordinates reflects an attempt by the characters of the novel to “rewrite” the time (history), master it, and recreate it. The focus is on the review of the novel characters’ words and on how important to them is the process of writing itself. The article puts forward the thesis of domination, applied by Eltang to describe artistically elements of the mythological world which is proved to exist by analyzing the characters’ names, by providing many examples of their ways of thinking and perceiving the world by saying phrases telling about myth images and legend creatures.